Collaboration and Learning: Reflections on Participation in “Empowering Global Futures” International School Social Work Conferences in Essex, UK - Leticia Villarreal Sosa; Marelize Vergottini; Stacy Gherardi (International Journal of School Social Work, 2025)
School social work continues to grow and make an impact across global contexts. The authors share their experiences and reflections after participation in the international school social work conference, “Empowering Global Futures: Strategies for School Social Work” held at Anglia Ruskin University, Chelmsford Campus, Essex, UK. The authors highlight speakers, global perspectives, practical applications, and emerging trends. Lastly, the authors make a “call to action” to advocate for increased and intentional efforts to reach across national boundaries to learn from each other and advance the knowledge base needed to address the needs of youth in schools in a global context.
Keywords: global school social work; international social work; anti-racist school social work; international collaboration; professional development